PERANAN ETIKA ANGGOTA SATUAN POLISI PAMONG PRAJA PROVINSI LAMPUNG DALAM MELAKSANAKAN SOSIALISASI PERATURAN GUBERNUR LAMPUNG NOMOR 45 TAHUN 2020 - Agus Purnomo; Supriyanto Supriyanto; Herman Naidi (Universitas Bandar Lampung (UBL), 2021)
Satuan Polisi Pamong Praja (Satpol PP) of Lampung Province with governor regulation No. 45 of 2020 conducts socialization so that the public can immediately know this so that it can comply. Ethics is considered to refer to two things, namely first, ethics with regard to disciplines that study the values embraced by man and his justification and in this case ethics is one of the branches of philosophy. Second, ethics is the subject matter in the discipline itself, namely the values of life and the laws that govern human behavior, morals.The results showed that: Ethics plays a role for members of the Satuan Polisi Pamong Praja Lampung Province in carrying out socialization. This result shows that if the Member applies good ethics and in accordance with the procedures set forth in the socialization of Governor Regulation No. 45 of 2020 concerning Guidelines for Adaptation of New Habits towards Productive and Safe Society corona virus disease 2019 (Covid-19), these aspects include external aspects and internal aspects, as well as implementing services to the community and effective and efficient management. These results show that the role of ethics in socializing is very influential to members and the community.